House prices and inflation: a cointegration analysis for Finland and Sweden - Bharat Barot; Kari Takala (Bank of Finland, 1998)
Given the emphasis on price stability in monetary policy, the concern caused by recent rapid increases in housing prices are understandable.It is suspected that such rises may provide early indication of mounting inflationary pressure.The purpose of this paper is to formulate and estimate an error-correction system model for housing prices and inflation for forecasting purposes.By using the estimated cointegrating vector, we also get an estimate of the equilibrium level for house prices that might be helpful in analysing the current situation in the housing market and the stance for monetary policy. Housing prices typically exhibit large cycles, and they are thus predictable to some extent.Volatility is caused by the fact that the supply of houses does not react perfectly to changes in housing demand.However, housing prices and inflation tend to have similar growth rates over the long run.In other words, houses provide a good inflation shelter, but in the long run, the real return to is equal to the explicit or implicit rental income derived from the owning of houses.The estimation results also show that the changes in the general price level are transmitted into house prices rather quickly, but inflation is surprisingly insensitive to housing prices.The equilibrium relationship between housing prices and consumer prices is also affected in the short run by variables such as interest rates, wages and the unemployment rate.
URN:NBN:fi:bof-20140807345
Keywords: 330; House prices; inflation; cointegration